2016
DOI: 10.30996/jpap.v2i02.1010
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kualitas Pelayanan Terhadap Kepuasan Pasien Peserta BPJS Di Puskesmas Pandian Kabupaten Sumenep

Abstract: Patient satisfaction as users of services is one indicator in assessing the quality of services at the health center. High satisfaction will show the success of the health center in providing quality health services. After a preliminary study showed that there are patients who are not satisfied with the services provided. The purpose of this study was to analyze the influence of service quality on patient satisfaction BPJS participants in Puskesmas Pandian Sumenep.Type of quantitative research. The study popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
1
1
0
1
Order By: Relevance
“…These results found that the average age of BPJS participants was in the age range of 40 years. These results are in line with research conducted at Sumenep that most of the BPJS class 1 participants are in the age range> 40 years (Rindi Antina, 2016). In general the characteristics of respondents are very influential in all behavioral behavior.…”
Section: Characteristics Of Respondentssupporting
confidence: 90%
“…These results found that the average age of BPJS participants was in the age range of 40 years. These results are in line with research conducted at Sumenep that most of the BPJS class 1 participants are in the age range> 40 years (Rindi Antina, 2016). In general the characteristics of respondents are very influential in all behavioral behavior.…”
Section: Characteristics Of Respondentssupporting
confidence: 90%
“…Health services at health centers or hospitals require indicators or benchmarks. According to Azwar in Antina (2016), it is generally formulated that the scope of health services is health services that can satisfy every service user according to the average level of satisfaction of the population and its implementation according to a predetermined code of ethics and standards.…”
Section: Resultsmentioning
confidence: 99%
“…157-166, Januari 2023 pelayanan berupa standar keahlian (profesi) untuk memenuhi kebutuhan dan keinginan pasien sehingga pasien dapat memperoleh kepuasan sehingga dapat meningkatkan kepercayaan pada pihak pemberi layanan melalui pelayanan yang prima. 26 Hasil observasi langsung yang telah dilakukan oleh peneliti bahwa petugas Puskesmas Poleang Barat mampu menumbuhkan kepercayaan dan keyakinan pasien terhadap pelayanan yang diberikan oleh Puskesmas. Misalnya pasien percaya kemampuan yang dimiliki oleh para petugas, bebas dari bahaya dan resiko, serta keraguan setiab pelayanan yang diberikan.…”
Section: Simpulanunclassified